(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
This prospective study was carried out in the Department of ENT and Head Neck Surgery, Sheikh Hasina medical college, Tangial, Bangladesh in a period of 6 months from January 2017 July 2017 among those complaining hearing loss attending in ENT out patient department. The aim of the study was to find the out pattern of hearing loss and hearing level comparison between noisy area (such as bazaar, bus stands, factory, school etc) to silent area. In this study 103 cases of hearing impaired people were taken and the data were collected by interviewing the cases as per questionnaire from history, examination and investigation report. Working place of most of the hearing impaired people was in noisy area 88 (85.4%). Among them most of the patients was male (58%) and female was (42%) and male:female ratio 1.4:1. The commonest type of hearing loss was sensorineural type. In the right ear 55 cases (53.4%) of sensorineural type deafness, 19 cases (18.4%) of mixed type of deafness and 21 cases (20.4%) of conductive type deafness. In the left ear 46 cases (47.7%) of sensorineural type deafness, 18 cases (17.5%) of mixed type deafness and 24 cases (23.3%) of conductive type deafness. This study showed that male (58%) were mostly affected than female (42%) and vehicle drivers (25.5%) were commonest group of people. From this study we got both ears were involved by disease process in 77.6% of patients and only right ear was 14.6% and only left ear was 10% of the patient of hearing loss. Bangladesh J Otorhinolaryngol; October 2017; 23(2): 159-163